Discussion on the cultivation of cyber security talents - Jian WENG; Linfeng WEI; Yue ZHANG (网络与信息安全学报)
The competition in cyberspace is ultimately the competition of talents.Nowadays,countries around the world pay great attention to the training of cyber security talents.the current situation of cyber security talents cultivation is introduced,the demand characteristics of cyber security talents are analyzed,and some suggestions for cyber security talents cultivation are put forward.Finally,some explorations on the training of cyber security talents in Jinan University are given.